Cryoradiotherapy for patients with locally advanced buccal skin cancer - I. N. Pustynskiy; A. I. Paches; S. I. Tkachev; M. A. Kropotov; S. D. Alieva; A. S. Yagubov; G. A. Bazhutova; S. V. Slanina (Сибирский онкологический журнал)
The new method of combined cryogenic and radiation therapy for patients with locally advanced buccal skin cancer was devised. The comprehensive analysis of results of cryoradiotherapy for 21 patients with basal cell and squamous cell buccal skin cancer (Т 2–4) and local recurrence was carried out. The treatment resulted in favorable long-term, cosmetic and functional results without local and general complications in these patients including elderly patients and patients with severe concomitant diseases